The Pengaruh Suplementasi Vitamin D Bagi Ibu Hamil: Indonesia - Rachel Putri Clarissa Lazuardi; Marina Astrid Rumawas; Diana Wijaya (Fakultas Kedokteran dan Ilmu Kesehatan Ukrida, 2023)
Large epidemiological studies reveal high prevalence of vitamin D deficiency in women, antenatal and breastfeeding mothers. Recent studies found role for vitamin D in pregnancy disorders and complications. This research is a literature review. Literatures was retrieved from Google Scholar, PubMed and Biomed Central, a total of 620 journals, after passing inclusion and exclusion factors, 13 journals were found to be appropriate. Research shows the association of vitamin D deficiency in pregnant women with pre-eclampsia, IUGR, recurrent miscarriage, placental inflammation, gestational diabetes mellitus and bacterial vaginosis. Ali etal, found that total incidence of pre-eclampsia was lower through vitamin D supplementation at dose of 4000 IU/day during pregnancy. Zerofsky etal, found 2000 IU/day during pregnancy more effective for improving vitamin D status and associated with reduced risk of recurrent miscarriage and IUGR. Yin etal, found that vitamin D 600 IU/day during pregnancy significantly reduced risk of GDM. Taheri etal, found a 63.5% BV cure rate with two drops (2000 IU)/day of vitamin D3 oily solution in pregnant women. There is associations between vitamin D deficiency, abnormalities and complications of pregnancy. Giving 2000 IU to pregnant women was good for preventing the risk of pregnancy disorders and drops as the best preparation.